COMPARISON OF THE EFFECTS OF REACTION PARAMETERS ON COLD FLOW PROPERTIES OF BIODIESE - ÖZGÜR, Ceyla; TOSUN, Erdi; ÖZGÜR, Tayfun (MATTER: International Journal of Science and Technology, 2017)
Biodiesel is biodegradable, renewable and nontoxic fuel source instead of petroleum fuel. Biodiesel has bad cold flow properties. The aim was to specify the optimum reaction parameters and obtain minimum cold flow properties. Transesterification method was preferred as the biodiesel production method. Reaction of transesterification is affected by diverse reaction parameters like as catalyst amount, molar ratio of alcohol to oil, time of reaction and temperature of reaction. In this experimental study, the impacts of operation parameters on cold flow properties of linseed oil biodiesel was compared. In production process potassium hydroxide (KOH) was chosen as catalyst and ethanol was used as alcohol. The impacts of catalyst amount (0.3-1.1 wt%), molar ratio of ethanol to oil (4:1-8:1), reaction time (45-105 min) and reaction temperature (50-65 ºC) was investigated. The minimum cold flow property values were obtained at 0.5% catalyst concentration, 7:1 molar ratio of ethyl alcohol to oil, 90 min of reaction time, 65ºC of reaction temperature. The lowest pour point, cloud point and cold filter plugging point of linseed biodiesel were found -10 ºC, -3 ºC, and -8 ºC, respectively at optimum reaction parameters.